Impact of Drinking Water and Sanitation Project on Local People in Damak Municipality, Ward Number 2 - Khadka, Himmat (New Journey, 2024)
This study was carried out among the users of Damak drinking water supply and sanitation system in Damak municipality, ward no. 2, Jhapa district. The primary objective of this study is to assess the impacts of the Drinking Water and Sanitation System project on the residents of Damak municipality area following its implementation. To achieve this goal, the study formulated research questions and employed a combination of qualitative and quantitative research methods. The study focused on analyzing and providing detailed explanations of the challenges related to drinking water, health, and sanitation facilities. Additionally, it extensively explored the transformations in the residents' lifestyles attributable to the project. The research design used in this study is both exploratory and descriptive data collection involved multiple methods, including observation, interviews and key-informant interviews.To achieve this goal, the study formulated research questions and employed a combination of qualitative and quantitative research methods. The study focused on analyzing and providing detailed explanations of the challenges related to drinking water, health, and sanitation facilities. Additionally, it extensively explored the transformations in the residents' lifestyles attributable to the project. The research design used in this study is both exploratory and descriptive data collection involved multiple methods, including observation, interviews and key-informant interviews. Primary data played a pivotal role in drawing valid conclusions, although some relevant secondary data were also incorporated.